Penerapan Metode Peer Group Teaching dalam Proses Pembelajaran Biologi untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa Kelas X SMA Negeri 3 Makassar - Palennari, Muhiddin; Hartati, .; Syamsiah, . (bionature, 2008)
This research is including pre experiment with aim to know improvement of activity of biological learning and improvement result of learning through applying of method peer group teaching. Research is done in class X SMA Negeri 3 Makassar at school year odd semester 2008/2009. Research design applied is pretest and post test group design. Before study with method peer group teaching, student is given pretest to know initial ability of student. Research data in the form of student activity is gathered by using observation sheet and data result of learning is gathered by using test result of learning is in the form of multiple choice. Data activity is analysed qualitatively while data result of pretest and post test is analysed with t-test. Result of research indicates that there are improvement significant between result of student learning before and after applying of method peer group teaching as well as existence of improvement of activity of student during study takes place. Â  Keywords: learning, peer group teaching, learning achievement, student activity